Divine Guidance In The Face Of Toxicity: How Islamic Leadership Navigates Workplace Stress And Mental Wellbeing In Higher Education Institutions - Bagis, Fatmah; Adawiyah, Wiwik Rabiatul (Universitas Mercu Buana, 2025)
Objectives: Concerns about mental health are currently in the workplace on the rise. This research endeavors to uncover how psychological distress mediates, and how perceived organizational support (POS) moderates, the effects of Islamic leadership and a toxic environment on mental health.Methodology: Participants are selected from among educators in three universities and a sample of 327. SEM-PLS aims to analyze the developed model.Finding: The evidence from the study supports the conclusion that Islamic leadership directly has a negative but significant impact on mental health, Islamic leadership can also indirectly benefit mental health by reducing psychological distress. Toxic environments significantly increase psychological distress. Toxic workplaces and mental health are positively mediated by psychological stress, which suggests that toxic workplace conditions exacerbate psychological distress in workers.Conclusion: The results demonstrated a relationship among the independent variable and Mental Health was significantly moderated by Perceived Organizational Support (POS). This investigation emphasizes importance of company support in fostering positive relationships and reducing negative effects on employees' mental health, highlighting the need to maintain a positive work atmosphere, use Islamic leadership principles.